The Efficacy of Using Round Table Technique in Teaching Writing Descriptive Text to Indonesian English as Foreign Language (EFL) Students - Yanpitherszon Liunokas (Institut Agama Islam Negeri Palopo, 2022)
This research aims at finding out the efficacy of using round table technique in teaching writing especially descriptive text to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of Round Table technique effective in teaching conditional sentences to Indonesian EFL students?. The research can be an addition to the persisting teaching writing in English particularly the descriptive text through the use of Round Table technique. This research was conducted at First semester students of the English Study Program of Nusa Cendana University, Kupang. The population of this research was First semester students of the English Study Program of Nusa Cendana University, Kupang. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in mastering writing descriptive text and the post-test given to find out the students’ improvement in mastering writing descriptive text after giving the treatment by using round table technique. The findings show that using round table technique is effective in teaching writing descriptive text to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use the round table technique in developing students’ writing descriptive of Indonesian EFL students.